Controlled Single Switch Step down AC/DC Converter without Transformer (International Journal of Engineering and Computer Science, 2014)
This paper presents a transformer less ac/dc converter which can be used in voltages between 90- 230 Vrms. Instead of a transformer, this topology consists of a buck dc/dc converter and a buck boost dc/dc converter. By the absence of transformer, reduce the complexity of converter and it is cost effective. Buck dc/dc converter keeps o/p voltage below the line voltage; limit the leakage current. By controlling the circuit with feedback, we can increasing the efficiency and reduce total harmonic distortion. Output voltage is 40 V with THD 12.36%. And output current is near 4 A. For further modification a feedback PI controller is used. After using PI controller THD is reduced to 6.231%.Thus using controlled circuit harmonic content is reduced and efficiency is improved. Working of the proposed circuit and verification by simulation results are discussed in this paper. MATLAB Simulation is done.